Reconstructing John Dewey's Educational Philosophy: Its Relevance to Democratic and Experiential Learning in Contemporary Education - Wardatul; Ahmad Syukri; Badarussyamsi; Boby Yasman Purnama (Darul Ilmi Bina Insan Foundation, 2025)
John Dewey remains one of the most influential figures in modern educational philosophy, particularly through his ideas on democracy, experiential learning, and the active role of learners in the educational process. Nevertheless, rapid developments in educational systems, digital learning environments, and increasingly complex social challenges require a renewed interpretation of Dewey's educational philosophy. This study aims to analyze the fundamental principles of John Dewey's educational thought and examine their relevance to contemporary educational practices. Employing a qualitative library research approach, this study critically analyzes Dewey's major works alongside relevant scholarly literature to construct a comprehensive understanding of his educational philosophy. The findings reveal that Dewey viewed education as a continuous process of reconstructing experience through active participation, reflective inquiry, and democratic interaction. He rejected traditional teacher-centered instruction that positions learners as passive recipients of knowledge and instead advocated learning through meaningful experiences, collaborative problem-solving, and critical thinking. The analysis further demonstrates that Dewey's educational philosophy remains highly relevant for addressing contemporary educational challenges, particularly in fostering student-centered learning, democratic school culture, creativity, and lifelong learning. This study contributes to the ongoing discourse on educational philosophy by providing a contextual reinterpretation of Dewey's ideas and highlighting their significance for developing more inclusive, participatory, and experience-based educational practices in the twenty-first century.